Bone health in childhood and adolescence: an overview on dual-energy X-ray absorptiometry scanning, fracture surveillance and bisphosphonate therapy for low-middle-income countries - Madhuchani, Dilki; Seneviratne, Sumudu Nimali; Ward, Leanne M. (Frontiers in Endocrinology, 2023)
Bone accrual in childhood determines bone health in later life. Loss of bone strength in early life can lead to increased morbidity and reduced quality of life in childhood and adolescence. Increased availability of assessment tools and bisphosphonate therapy, together with increased awareness on the significance of fracture history and risk factors, have led to greater opportunities, to improve detection and optimize management of children and adolescents with bone fragility globally, including those in lower resource settings. Bone mineral density z-scores and bone mineral content are surrogate measures of bone strength, which can be measured by dual-energy X-ray absorptiometry (DXA), in growing individuals. DXA can aid in the diagnosis and management of primary and secondary bone fragility disorders in childhood. DXA helps evaluate children with clinically significant fractures, and monitor those with bone fragility disorders, or at high risk for compromised bone strength. Obtaining DXA images can however be challenging, especially in younger children, due to difficulty in positioning and movement artefacts, while paediatric DXA interpretation can be confounded by effects of growth and puberty. Furthermore, access to DXA facilities as well as appropriate paediatric reference norms and expertise for interpretation, may not be easily available especially in lower resource settings. Pediatric bone experts are now placing increasing emphasis on the fracture phenotype and clinical context to diagnose osteoporosis over bone mineral density (BMD) by DXA. Low trauma vertebral fractures are now recognized as a hallmark of bone fragility, and spinal fracture surveillance by either conventional lateral thoracolumbar radiographs or vertebral fracture assessment by DXA is gaining increasing importance in diagnosing childhood osteoporosis, and initiating bone protective therapy. Furthermore, it is now understood that even a single, low-trauma long bone fracture can signal osteoporosis in those with risk factors for bone fragility. Intravenous bisphosphonate therapy is the mainstay of treatment for childhood bone fragility disorders. Other supportive measures to improve bone strength include optimizing nutrition, encouraging weight bearing physical activity within the limits of the underlying condition, and treating any associated endocrinopathies. With this paradigm shift in childhood osteoporosis evaluation and management, lack of DXA facilities to assess BMD at baseline and/or provide serial monitoring is not a major barrier for initiating IV bisphosphonate therapy in children in whom it is clinically indicated and would benefit from its use. DXA is useful, however, to monitor treatment response and optimal timing for treatment discontinuation in children with transient risk factors for osteoporosis. Overall, there is lack of awareness and paucity of guidelines on utilizing and adopting available resources to manage paediatric bone disorders optimally in lower-resource settings. We provide an evidence-based approach to the assessment and management of bone fragility disorders in children and adolescents, with appropriate considerations for lower resource settings including LMIC countries.